Methodological approach of studying religious ethics of other faiths between Ismail Al-Faruqi and Toshihiko Izutsu: a comparative study - Hashi, Abdurezak Abdulahi (2008)
Both Toshihiko Izutsu and Ismail al-Faruqi have studied religious ethics, but according to their respective religious faiths. In his Christian Ethics al-Faruqi analyzed Christian ethics and moral values and presented a twofold methodology on which, according to him, religious principles including ‘religious ethics’ could be objectively analyzed and understood. Likewise, in his monumental work: Ethico-Religious Concepts in the Qur’an, Toshihiko provides a semantic analysis of the Qur’anic ethico-religious terms, and presents an exposition of ‘methodological principles’ of studying objectively the ethical terms of other religions. Both al-FÉrËqÊ and Toshihiko stress that the polemical and argumentative approaches of religious terms of other faiths including ethics are counterproductive and generate only mistrust between the believers and the researcher. Thus, an objective and meaningful study of religious ethics of other faiths, according to them, is achievable only through analyzing ethical terms from and within the religious structure that they belong to. In the introductory remarks of his book, Toshihiko states that the methodological approach of his presentation of the Qur’anic ethico-religious concepts lies in the analytic method that he applies to the Qur’anic data, which is to make the Qur’an interpret its own concepts and speak for itself. Similarly, al-Faruqi states that his aim in studying Christian ethics is not to present an Islamic critique of Christian ethical values but pure and simple presentation of Christian ethics drawn from the Christian tradition, so that a Christian reader will not offer to brush aside this work as the opinion of a non-Christian. However, though these two approaches of studying religious ethics seem to be indistinguishable in terms of objectivity and neutrality, nonetheless, there are some fundamental divergences between them in terms of style and aim. This paper is an attempt to offer comparative analysis on the methodological approaches of the two scholars’ study of religious ethics.